Heterogeneity of blood processing and storage additives in different centers impacts stored red blood cell metabolism as much as storage time: lessons from REDS‐III—Omics. Issue 1 (24th October 2018) - D'Alessandro, Angelo; Culp‐Hill, Rachel; Reisz, Julie A.; Anderson, Mikayla; Fu, Xiaoyun; Nemkov, Travis; Gehrke, Sarah; Zheng, Connie; Kanias, Tamir; Guo, Yuelong; Page, Grier; Gladwin, Mark T.; et al.
Abstract : BACKGROUND: Biological and technical variability has been increasingly appreciated as a key factor impacting red blood cell (RBC) storability and, potentially, transfusion outcomes. Here, we performed metabolomics analyses to investigate the impact of factors other than storage duration on the metabolic phenotypes of stored RBC in a multicenter study. STUDY DESIGN AND METHODS: Within the framework of the REDS‐III (Recipient Epidemiology and Donor Evaluation Study‐III) RBC‐Omics study, 13, 403 donors were enrolled from four blood centers across the United States and tested for the propensity of their RBCs to hemolyze after 42 days of storage. Extreme hemolyzers were recalled and donated a second unit of blood. Units were stored for 10, 23, and 42 days prior to sample acquisition for metabolomics analyses. RESULTS: Unsupervised analyses of metabolomics data from 599 selected samples revealed a strong impact (14.2% of variance) of storage duration on metabolic phenotypes of RBCs. The blood center collecting and processing the units explained an additional 12.2% of the total variance, a difference primarily attributable to the storage additive (additive solution 1 vs. additive solution 3) used in the different hubs. Samples stored in mannitol‐free/citrate‐loaded AS‐3 were characterized by elevated levels of high‐energy compounds, improved glycolysis, and glutathione homeostasis. Increased methionine metabolism and activation of the transsulfuration pathway was noted in samples processed in the center using additive solution 1. CONCLUSION: Blood processing impacts the metabolic heterogeneity of stored RBCs from the largest multicenter metabolomics study in transfusion medicine to date. Studies are needed to understand if these metabolic differences influenced by processing/storage strategies impact the effectiveness of transfusions clinically.